A= 1/2+1/2^2+1/2^3+...+1/2^13+1/2^14
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,=\(\dfrac{8}{14}-\dfrac{1}{14}+\dfrac{5}{21}+\dfrac{3}{2}\)
=\(\dfrac{1}{2}+\dfrac{3}{2}+\dfrac{5}{21}\) =\(2+\dfrac{5}{21}\) =\(\dfrac{42}{21}+\dfrac{5}{21}\) =\(\dfrac{47}{21}\)
b,=\(\dfrac{11}{13}.\dfrac{12}{15}-\dfrac{7}{15}+\dfrac{14}{15}.\dfrac{11}{13}\)
=\(\dfrac{11}{13}.\left(\dfrac{12}{15}+\dfrac{14}{15}\right)-\dfrac{7}{15}\)
=\(\dfrac{11}{13}.\dfrac{26}{15}-\dfrac{17}{15}\) =\(\dfrac{22}{15}-\dfrac{17}{15}\) =\(\dfrac{5}{15}\) =\(\dfrac{1}{3}\)
c,=\(\left(\dfrac{3}{6}-\dfrac{2}{6}\right)^2\) =\(\left(\dfrac{1}{6}\right)^2\) =\(\dfrac{1}{36}\)
d,=câu này dễ mà
![](https://rs.olm.vn/images/avt/0.png?1311)
\(A=\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{13}}+\frac{1}{2^{14}}\)
\(\Leftrightarrow2A=2\left(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{13}}+\frac{1}{2^{14}}\right)\)
\(\Leftrightarrow2A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{12}}+\frac{1}{2^{13}}\)
\(\Leftrightarrow2A-A=\left(1+\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+....+\frac{1}{2^{12}}+\frac{1}{2^{13}}\right)-\left(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{13}}+\frac{1}{2^{14}}\right)\)
\(\Leftrightarrow A=1-\frac{1}{2^{14}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{2}{5}+\dfrac{3}{5}\cdot\dfrac{10}{3}\cdot\dfrac{1}{2}=\dfrac{2}{5}+\dfrac{10}{5}\cdot\dfrac{1}{2}=\dfrac{2}{5}+1=\dfrac{7}{5}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2/9 - (1/20 + 2/9)
= 2/9 - 1/20 - 2/9
= (2/9 - 2/9) - 1/20
= 0 - 1/20
= -1/20
b) -3/14 + 2/13 + (-25/14) + (-15/13)
= (-3/14 - 25/14) + (2/13 - 15/13)
= -2 - 1
= -3
c) -3/11 + 11/8 - 3/8 + (-8/11)
= (-3/11 - 8/11) + (11/8 - 3/8)
= -1 + 1
= 0
d) 3/8 + (-1/4) - (7/12 - 1/6)
= 1/8 - 5/12
= -7/24
e) (1/3 + 12/67 + 13/41) - (79/67 - 28/41)
= 1/3 + 12/67 + 13/41 - 79/67 + 28/41
= 1/3 + (12/67 - 79/67) + (13/41 + 28/41)
= 1/3 - 1 + 1
= 1/3
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{3}{5}:\left(-\frac{1}{15}-\frac{1}{6}\right)+\frac{3}{5}:\left(-\frac{1}{3}-1\frac{1}{15}\right)\)
\(=\frac{3}{5}:\left(-\frac{1}{15}-\frac{1}{6}-\frac{2}{6}-1+\frac{1}{15}\right)\)
\(=\frac{3}{5}:\left(-\frac{1}{2}-1\right)\)
\(=\frac{3}{5}:\left(-\frac{3}{2}\right)\)
\(=-\frac{2}{5}\)
b) \(\left(-\frac{3}{4}+\frac{5}{13}\right):\frac{2}{7}-\left(2\frac{1}{4}+\frac{8}{13}\right):\frac{2}{7}\)
\(=\left(-\frac{3}{4}+\frac{5}{13}-2+\frac{1}{4}+\frac{8}{13}\right):\frac{2}{7}\)
\(=\left(-\frac{1}{2}+1-2\right):\frac{2}{7}\)
\(=\left(-\frac{1}{2}-1\right):\frac{2}{7}\)
\(=-\frac{3}{2}:\frac{2}{7}\)
\(=-\frac{21}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(2A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{12}}+\frac{1}{2^{12}}\)
\(2A-A=\left(1+\frac{1}{2}+\frac{1}{2^2}+....+\frac{1}{2^{12}}+\frac{1}{2^{13}}\right)-\left(\frac{1}{2}+\frac{1}{2^2}+\frac{1}{2^3}+...+\frac{1}{2^{13}}+\frac{1}{2^{14}}\right)\)
\(A=1-\frac{1}{2^{14}}\)
Vậy \(A=1-\frac{1}{2^{14}}\)